2002
DOI: 10.1093/emboj/cdf576
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced decrease in TRAF2 stability is mediated by Siah2

Abstract: TRAF2 serves as a central regulator of the cellular response to stress and cytokines through the regulation of key stress-signaling cascades. Here we demonstrate that wild-type, but not RING mutant, Siah2 targets TRAF2 for ubiquitylation and degradation in vitro. Siah2 mediates equally ef®cient ubiquitylation of RING mutant TRAF2. In vivo, Siah2 primarily targets TRAF2 for degradation under stress conditions. Tumor necrosis factor-a (TNF-a) and actinomycin D treatment results in accelerated TRAF2 degradation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
115
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 46 publications
2
115
0
Order By: Relevance
“…We next determined whether tumorigenesis and metastasis of melanoma cells would be affected upon inhibition of Siah2 ligase activity by a RING mutant (S2RM), a potent dominant-negative form of Siah2 (6). Stable expression of S2RM in SW1 cells (SW1 S2RM ) was confirmed in immunoblot analysis (Fig.…”
Section: Effect Of Siah2 On Metastasis Of Sw1 Melanoma Cells Is Hif-1␣-mentioning
confidence: 97%
See 1 more Smart Citation
“…We next determined whether tumorigenesis and metastasis of melanoma cells would be affected upon inhibition of Siah2 ligase activity by a RING mutant (S2RM), a potent dominant-negative form of Siah2 (6). Stable expression of S2RM in SW1 cells (SW1 S2RM ) was confirmed in immunoblot analysis (Fig.…”
Section: Effect Of Siah2 On Metastasis Of Sw1 Melanoma Cells Is Hif-1␣-mentioning
confidence: 97%
“…Somewhat similar to PHYL is Siahinteracting protein (SIP), which interacts with Siah within the same structural domain (3,4). In mammals, two isoforms, Siah1 and Siah2 (5), have been shown to control the stability of several substrates, including nuclear corepressor, ␤-catenin, TRAF2, ␣-ketoglutarate dehydrogenase, and prolyl hydroxylase 3 (PHD3), thereby affecting diverse cellular functions, such as signaling, survival, and mitochondrial biogenesis (6)(7)(8)(9)(10). We have demonstrated that by regulating PHD3 stability, Siah2 contributes to the abundance of hypoxia-inducible factor (HIF)-1␣, thereby playing an important role in the cellular response to hypoxia (9).…”
mentioning
confidence: 99%
“…Expression vectors for cIAP-1 and cIAP-2 were kindly provided by Dr John C. Reed (Burnham Institute, La Jolla, CA, USA) (Deveraux et al, 1998). The TRAF-2 expression vector was provided by Dr Ze'ev Ronai (Ruttenberg Cancer Center, Mount Sinai School of Medicine, New York, NY, USA) (Habelhah et al, 2002). Note that the substitution of an asparagine ( ¼ N) residue for the amino acid at position 17 of small GTPases Cdc42 and Rac1 (position 19 for Rho) reduces their affinity for GTP, thus creating dominant-negative mutants (Egan and Weinberg, 1993).…”
Section: Expression Vectors and Cell Transfectionsmentioning
confidence: 99%
“…Interestingly, one of these proteins targeted by SIAH is TRAF2. Indeed, SIAH interacts with TRAF2 through its TD and catalyzes its ubiquitination and degradation under stress conditions 111 .…”
Section: Viral Immune Evasion Strategies Interfering With Math-dependmentioning
confidence: 99%